PENGEMBANGAN ORGANISASI BERBASIS KOMPETENSI (SEBUAH KAJIAN TEORI) - Samuel Atbar (Papsel Journal of Humanities and Policy, 2024)
Every organisation must be able to compete and process with all the resources available to it to develop and grow the organisation.   One of the organisational development strategies carried out is based on performance competencies in the hope of remaining competitive and developing the organisation to achieve the organisation's goals. Thus the purpose of this research is to find out about how the design of performance competencies in an effort to develop the organisation as a whole. The method used in writing this article is literature review or literature review.  The result of this research is that in practice organisational development competencies are carried out in order to monitor and improve the organisation to work in accordance with expectations for the achievement of organisational goals.   Keywords: Development, Organisation, Competence